2016
DOI: 10.1177/1740774516643689
|View full text |Cite
|
Sign up to set email alerts
|

A post hoc evaluation of a sample size re-estimation in the Secondary Prevention of Small Subcortical Strokes study

Abstract: Background/Aims The use of adaptive designs has been increasing in randomized clinical trials. Sample size re-estimation is a type of adaptation in which nuisance parameters are estimated at an interim point in the trial and the sample size re-computed based on these estimates. The Secondary Prevention of Small Subcortical Strokes (SPS3) study was a randomized clinical trial assessing the impact of single vs. dual antiplatelet therapy and control of systolic blood pressure to a higher (130-149 mmHg) vs. lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…Although the statistical and clinical trial literature has many examples of work to theoretically evaluate sample size re-estimation methods and performance through simulation, there have been few examples from real-world applications to detail the implementation and impact of adaptations, particularly from trials utilizing blinded sample size re-estimation [1, 2, 25]. McClure et al provide a detailed review of their re-estimation procedure and trial results from a trial of secondary prevention of small subcortical stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the statistical and clinical trial literature has many examples of work to theoretically evaluate sample size re-estimation methods and performance through simulation, there have been few examples from real-world applications to detail the implementation and impact of adaptations, particularly from trials utilizing blinded sample size re-estimation [1, 2, 25]. McClure et al provide a detailed review of their re-estimation procedure and trial results from a trial of secondary prevention of small subcortical stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of sample size re-estimation procedures, following the completion of a clinical trial, has been sparsely reported in the literature [1, 2]. Based on the acknowledgment of uncertainty in the information used as a basis for sample size determination at the design stage, various methods of re-evaluation of sample size have been developed [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the clinical trial sponsor has a number of factors to consider regarding SSR application [ 12 ]. The use of AD, including SSR, can be beneficial in many circumstances, but the benefit may not be applicable in all cases, meaning that factors such as the statistical impact and the trial cost need to be considered [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental idea of a response‐adaptive design is to use the responses of the patients already enrolled in the clinical study to skew the treatment allocation probabilities to reach the predefined objective, such as a reduction of the number of patients who receive the inferior treatment. Because of its attractive properties, adaptive design is currently considered a viable option in many areas of clinical research and mainstream drug development . For example, in the field of global health, the appalling fatality rate of the West African Ebola epidemic in 2014 triggered more discussions of the benefits of an adaptive design for related clinical studies to lower the mortality rate …”
Section: Introductionmentioning
confidence: 99%